Heat island effects in urban life cycle assessment: Novel insights to include the effects of the urban heat island and UHI‐mitigation measures in LCA for effective policy making. (21st January 2020) - Susca, Tiziana; Pomponi, Francesco
Abstract: Urbanization often entails a surge in urban temperature compared to the rural surroundings: the Urban Heat Island (UHI) effect. Such a temperature increase triggers the formation of pollutants worsening the urban air quality. Jointly, bad air quality and UHI affect ecosystems and human health. To alleviate the impacts on the population and the environment, it is crucial to design effective UHI‐mitigation measures. Life Cycle Assessment (LCA) is an assessment tool able to capture the complexity of urban settlements and quantify their impact. Yet, as currently implemented, LCA neglects the interactions between the built environment and the local climate, omitting the resulting impacts. This study reviews the existing literature, showing the lack of studies that organically include interactions between the built environment and local climate in LCA. This forms the basis to identify the unsuitability of the current LCA framework for comprehensively capturing the impact of urban settlements. To overcome this limitation, this research offers a pathway to expand the LCA methodology, indicating the necessity to (a) couple the LCA methodology with climate models or physical relations that quantify the interactions between the local climate and the built environment; (b) include novel impact categories in LCA to address such interactions; and (c) use existing or ad hoc developed characterization factors to assess the impacts related to the UHI effect. The LCA community can build on the frame of reference offered by this research to overcome the current limitations of LCA and enable its use for a comprehensive assessment of the impacts of UHI and its mitigation measures.